The Influence of Water Vapor on the Stability and Processing of Hybrid Perovskite Solar Cells Made from Non‐Stoichiometric Precursor Mixtures. Issue 18 (14th September 2016) - Petrus, Michiel L.; Hu, Yinghong; Moia, Davide; Calado, Philip; Leguy, Aurélien M. A.; Barnes, Piers R. F.; Docampo, Pablo
Abstract: We investigated the influence of moisture on methylammonium lead iodide perovskite (MAPbI3 ) films and solar cells derived from non‐stoichiometric precursor mixtures. We followed both the structural changes under controlled air humidity through in situ X‐ray diffraction, and the electronic behavior of devices prepared from these films. A small PbI2 excess in the films improved the stability of the perovskite compared to stoichiometric samples. We assign this to excess PbI2 layers at the perovskite grain boundaries or to the termination of the perovskite crystals with Pb and I. In contrast, the MAI‐excess films composed of smaller perovskite crystals showed increased electronic disorder and reduced device performance owing to poor charge collection. Upon exposure to moisture followed by dehydration (so‐called solvent annealing), these films recrystallized to form larger, highly oriented crystals with fewer electronic defects and a remarkable improvement in photocurrent and photovoltaic efficiency. Abstract : Moisture in moderation : The effect of moisture on hybrid methylammonium lead iodide (MAPbI3 ) perovskite films and solar cells prepared from nonstoichiometric precursor solutions is presented. A small PbI2 excess is found to decelerate moisture‐induced degradation compared to stoichiometric samples. Devices containing excess MAI with initially poor efficiencies show a remarkable increase in performance after exposure to moisture owing to a recrystallization process.